IMPLEMENTASI PASAL 504-505 KUHP DAN PERDA NO. 2 TAHUN 2008 TERHADAP PEMBINAAN TUNAWISMA DI KOTA MAKASSAR - Adriana Mustafa (Universitas Islam Negeri Alauddin Makassar, 2021)
The main problem in this research is regarding the application of Article 504 – 505 of the Criminal Code and Regional Regulation Number 2 of 2008 against the Homeless in Makassar City, then formulated into a sub-problem or research question, namely what factors cause the emergence of homelessness in Makassar City and how to apply Article 504 – 505 of the Criminal Code against the Homeless? This research uses qualitative field research. The results of this study indicate that the factors that cause the emergence of homelessness are Poverty Problems, Education Problems, Work Skills Problems and Social Cultural Problems and Social Cultural Problems Consisting of Low Self-Esteem, Surrender to Physical Conditions, Health Problems. The application of Articles 504 – 505 of the Criminal Code has been implemented but has not been maximized, so this effort is not optimal enough, this is what makes the homeless still carry out their activities for economic needs. The implication of the research is that the South Sulawesi Provincial Social Service Government is expected to collect data on the homeless who do not have a place to live, build rehabilitation homes or develop work skills. It is advisable for the Makassar City DPRD Government to strengthen the sanctions given to the homeless in accordance with Articles 504 – 505 of the Criminal Code and Regional Regulation Number 2 of 2008.